Potensi Kayu Manis sebagai Obat untuk Meredakan Nyeri Haid: Literature Review - Ari Kusuma Yana, I Gusti Agung; Lilis Adnyani, Ni Putu; Sari, Gusti Ayu Putu Laksmi Puspa (Usadha, 2024)
According to the World Health Organization (WHO), in 2015, globally, an average of more than 50% of women experienced menstrual pain. The recorded incidence of menstrual pain or dysmenorrhea in Indonesia is 64.25%, which includes primary dysmenorrhea (54.89%) and secondary dysmenorrhea (9.36%). Menstrual pain is a common menstrual symptom in women who menstruate. This condition is characterized by cramps and cramps, colicky pain in the lower abdomen which disrupts daily activities. Menstrual pain may be caused by excessive or unbalanced levels of prostanoids and eicosanoids released from the endometrium during menstruation.